Is your resurrection too small? - Hovey, Craig (Theology, 2010)
This article asks about the kind of knowledge appropriate to Christ's resurrection and attempts to preserve its mystery against modern habits of knowing. Such habits inscribe a distance from the resurrection as event, tempting theology to enlist the resurrection in a larger set of arguments and proofs of something else like the reliability of Scripture's witness. As such, they diminish more generally all witness to contingent history. In contrast, this article finds a resource in Thomas Aquinas' claim that the resurrection is ‘fitting’, a judgement that Christians can only claim after the fact and perform in the work of worship and liturgy.